User-Centric Joint Admission Control and Resource Allocation for 5G D2D Extreme Mobile Broadband: A Sequential Convex Programming Approach - Tang, Rui; Zhao, Jihong; Qu, Hua; Zhang, Zhenwei (IEEE communications letters, 2017)
Device-to-Device (D2D) communication has been recognized as a promising remedy to offload 5G extreme mobile broadband services by utilizing the favorable channel condition in proximity. In contrast to most literature emphasizing system-centric metrics, we optimize user-centric ones, including the number of admitted D2D links with satisfied quality-of-service requirement and power consumption, by integrating resource allocation with admission control. Due to the intractability of the above problem, we apply the sequential convex programming technique to achieve a reasonable approximation to the original optimum. Simulations verify the advantages of conducting user-centric optimizations and show the efficacy of our scheme.